2008
DOI: 10.1007/s12011-008-8202-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Oxidative Status of the 2-Furan-2-yl-1H-Benzimidazole in Rats

Abstract: We investigated the influence of 2-furan-2-yl-1H-benzimidazole regarding vitamins A, E, C, selenium (Se), malondialdehyde (MDA), and glutathione peroxidase (GSH-Px) levels on rats. 2-Furan-2-yl-1H-benzimidazole was given to rats by subcutaneous injection every other day for a total of 22 injections. At the end of the experiment, Se levels were determined by using a fluorimetric method. Serum levels of vitamins A, E, C, and malondialdehyde (MDA) were determined by high-performance liquid chromatography. Glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…It also causes a significant decline in the levels of glutathione, catalase, GSH-Px, and Cu-Zn superoxide dismutase in rats [160]. The impact of 2-furan-2-yl-1H-benzimidazole on vitamins A, E, C, and Se, malondialdehyde, and glutathione peroxidase levels on rats was analysed in a study by Karatas et al [161]. The results showed that vitamins A, E, C, and Se levels were lower than the control groups, while serum MDA level and GSH-Px activity flexibly increased, depending on the injection days.…”
Section: Purposementioning
confidence: 99%
“…It also causes a significant decline in the levels of glutathione, catalase, GSH-Px, and Cu-Zn superoxide dismutase in rats [160]. The impact of 2-furan-2-yl-1H-benzimidazole on vitamins A, E, C, and Se, malondialdehyde, and glutathione peroxidase levels on rats was analysed in a study by Karatas et al [161]. The results showed that vitamins A, E, C, and Se levels were lower than the control groups, while serum MDA level and GSH-Px activity flexibly increased, depending on the injection days.…”
Section: Purposementioning
confidence: 99%
“…We found that MDA levels in serum, liver, and kidney increased compared with control groups at all injection times after rats had been injected with 3-(1H-pyrrol-2-yl)-1H-indazole. Increased MDA might be an indicator of lipid peroxidation, as previously suggested [27][28][29][30]. While vitamins A, E, and C levels decrease, MDA level increase in liver and kidney from the third injection can be a sign of maximum of stress.…”
Section: Discussionmentioning
confidence: 64%
“…Decreased antioxidant vitamin levels might be a result of getting more metabolic stress because vitamins A, C, E, and Se are major non-enzymatic antioxidants in the body [32]. Several previous studies have shown that increasing MDA levels occur as vitamins A, E, and C levels decrease in the serum of the rat [28,29], mainly because vitamins A and C, like α-tocopherol, prevent lipid peroxidation by trapping the free radicals. Vitamin C regenerates α-tocopherol from α-tocopheroxyl radical [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The results of research carried out in recent years indicate that anthelmintic drugs cause oxidative stress (Karatas et al 2008, Pinlaor et al 2008, Dewa et al 2009). Ince et al (2010) demonstrated in research on rats that levamisole administered at a dose of 20 mg/kg bw for 7 days caused oxidative stress and peroxidase activity.…”
Section: Discussionmentioning
confidence: 99%